2020
DOI: 10.1101/2020.11.30.403303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thede novogenome of the “Spanish” slugArion vulgarisMoquin-Tandon, 1855 (Gastropoda: Panpulmonata): massive expansion of transposable elements in a major pest species

Abstract: Background: The "Spanish" slug, Arion vulgaris Moquin-Tandon, 1855, is considered to be among the 100 worst pest species in Europe. It is common and invasive to at least northern and eastern parts of Europe, probably benefitting from climate change and the modern human lifestyle. The origin and expansion of this species, the mechanisms behind its outstanding adaptive success and ability to outcompete other land slugs are worth to be explored on a genomic level. However, a high-quality chromosome-level genome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…1 ). The topology of the species tree inferred is as described in Chen et al (2020) : Patellogastropoda is sister to all other gastropods with a low support (PP = 0.66), and the alternative topologies of Patellogastropoda being sister to Vetigastropoda + Neomphalina (PP = 0.27), Patellogastropoda sister to Heterobranchia + Caenogastropoda (PP = 0.07) even less likely ( Fig. 2 , Fig.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…1 ). The topology of the species tree inferred is as described in Chen et al (2020) : Patellogastropoda is sister to all other gastropods with a low support (PP = 0.66), and the alternative topologies of Patellogastropoda being sister to Vetigastropoda + Neomphalina (PP = 0.27), Patellogastropoda sister to Heterobranchia + Caenogastropoda (PP = 0.07) even less likely ( Fig. 2 , Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Our results support this hypothesis: excluding C. consors , we got a total of 847 SOGs (767,180 sites) among the rest of the 15 species, increasing SOG numbers 2.15 times. Then we used the 847 SOGs for phylogenetic reconstruction using a concatenation method and compared it with Chen et al (2020) who used 233 SOGs (158,094 sites) identified in all 16 species. In contrast to Chen et al (2020) , Patellogastropoda clustered as sister to Vetigastropoda plus Neomphalina with a highly increased support (bootstrap value 89 compared to 48) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations